A novel tamoxifen-inducible Mct8-CreERT2 mouse model for targeted studies of Mct8-expressing cells and thyroid hormone transport and function - Anna Molenaar; Noémi Mallet; Marin Bralo; Luciano J. Hoeher; Sonja C. Schriever; Ekta Pathak; Miriam Bernecker; Timo D. Müller; Ali Ertürk; Alberto Cebrian-Serrano; Paul T. Pfluger (Transgenic Research, 2025)
Deficiency of the Monocarboxylate Transporter 8 (MCT8) severely impairs thyroid hormone (TH) transport into the brain, disrupting brain development as well as peripheral TH homeostasis. Studies assessing MCT8 expression patterns and tissue-specific pathologies induced by local TH-deficiency are often inconclusive due to unreliable antibody staining and the lack of functional tools to specifically target MCT8-expressing cells. For this purpose, we generated non-inducible Mct8-Cre and tamoxifen-inducible Mct8-CreERT2 mice. Mct8-Cre;Sun1-sfGFP mice demonstrated ubiquitous Sun1-sfGFP expression, due to early recombination driven by Mct8 gene expression at the stage of trophoblast implantation. Tamoxifen injection in 6-week-old Mct8-CreERT2 mice induced reporter expression specifically in Mct8-expressing cells in the brain and peripherally in liver, kidney, and thyroid, without leaky reporter expression in vehicle controls. Using vDISCO tissue clearing and 3D-imaging of GFP-nanobody-boosted mice, we further identified the sublingual salivary gland and the prostate as prominent Mct8-expressing organs. Nuclei from Mct8-expressing cells in the brain could selectively be enriched using fluorescence-activated nuclei sorting on Mct8-CreERT2;Sun1-sfGFP mice and characterized as choroid plexus cells and tanycytes. Our new inducible Mct8-CreERT2 line provides researchers with a tool to reliably mark, enrich, and characterize Mct8-expressing cells and to genetically modify genes specifically in these cells to study thyroid hormone transport and function.

Single-Cell Transcriptome Analysis Reveals the Role of Pancreatic Secretome in COVID-19 Associated Multi-organ Dysfunctions - Ekta Pathak; Neelam Atri; Rajeev Mishra (Interdisciplinary Sciences: Computational Life Sciences, 2022)